Effects of maternal exposure to the galactagogue Sulpiride on reproductive parameters in female rats - Camin, Nathalia de Azevedo; Vieira, Milene Leivas; Montagnini, Bruno Garcia; Inhasz Kiss, Ana Carolina [UNESP]; Ceccatto Gerardin, Daniela Cristina (Elsevier B.V., 2015)
The antipsychotic Sulpiride has been documented as an effective galactagogue that acts blocking dopamine receptors, increasing prolactin concentrations. However, this drug passes through the milk exposing neonates during postnatal development, which may result in functional and morphological alterations in adult life. Therefore, the aim of this study was to investigate whether maternal exposure to Sulpiride during lactation could impair reproductive development of female offspring. The dams were treated daily by gavage with Sulpiride doses of 2.5 mg/Kg (SUL 2.5 mg group) and 25 mg/Kg (SUL 25 mg group), or distilled water (Control group) throughout the lactation period. During early life, body weight, anogenital distance, and vaginal opening were analyzed on the female offspring. In adulthood, estrous cycle, sexual behavior, estrogen levels as well as the weight of the reproductive organs were evaluated. There were no differences regarding body weight, anogenital distance, puberty onset, frequency and duration of the estrous cycle and estradiol levels on female offspring. Nonetheless, there were changes in sexual behavior. There was an increase in the number of observations in reflex magnitude 0 (absence of lordosis) and reflex magnitude 2 as well as a reduction of reflex magnitude 3 in the rats of SUL 25 mg group in relation to the Control group, suggesting a decrease in sexual receptivity of these animals. These results demonstrate that maternal exposure to Sulpiride can alter reproductive function in female offspring rats. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Dopaminergic antagonist; Sexual behavior; Estrous cycle; Rat